Antara Estetika dan Fungsi: Negosiasi Tren Fashion Korea di Kalangan Remaja Makassar: Between Aesthetics and Function: Negotiating Korean Fashion Trends Among Makassar Youth - Irma Irma (Universitas Muslim Maros, 2026)
The Korean Wave phenomenon has transformed the lifestyle landscape of adolescents in Indonesia; however, previous studies have tended to focus on visual adoption and the influence of social media without examining the mechanisms of material negotiation in everyday life. This study aims to explore how adolescents in Makassar negotiate Korean fashion aesthetics with local functional needs and the implications for their consumption behavior. This qualitative research was conducted in Makassar. Participant observation and in-depth interviews are combined data collection methods. There six informants involved in this study and they are adolescents aged between 17 and 25 years. This study reveals that the adoption of Korean trends is not achieved through passive imitation, but rather through a process of material glocalization. The findings indicate that while the “clean look” and elegant aesthetics are the main attractions, adolescents actively modify their choice of clothing materials for comfort in a tropical climate and to comply with local norms of modesty. Furthermore, exposure to social media triggers consumption behaviour through FoMO mechanism. However, there is strong individual agency in curating trends to ensure they remain functional. It is argued in this article that adolescents act as glocal actors who “domesticate” transnational aesthetics to align modern identity with local cultural realities.